2010
DOI: 10.1007/s10899-010-9204-2
|View full text |Cite
|
Sign up to set email alerts
|

Reports of Wins and Risk Taking: An Investigation of the Mediating Effect of the Illusion of Control

Abstract: Two experiments examined the relationships between the knowledge that another person has won in a gamble, the illusion of control and risk taking. Participants played a computer-simulated French roulette game individually. Before playing, some participants learnt that another person won a large amount of money. Results from a first experiment (n = 24) validated a causal model where the knowledge of another person's win increased the illusion of control, measured with betting times, expectancy and self-reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…However, if the participant did not meet the goal, the participant had that same amount deducted from his or her daily steps (−500 steps). This game feature was implemented based on risk‐taking theory, which suggests that people are more likely to engage in a challenge if they believe they have a realistic chance of receiving a payoff 26, 27. The individual could also choose not to accept the challenge.…”
Section: Methodsmentioning
confidence: 99%
“…However, if the participant did not meet the goal, the participant had that same amount deducted from his or her daily steps (−500 steps). This game feature was implemented based on risk‐taking theory, which suggests that people are more likely to engage in a challenge if they believe they have a realistic chance of receiving a payoff 26, 27. The individual could also choose not to accept the challenge.…”
Section: Methodsmentioning
confidence: 99%
“…Correcting erroneous beliefs is in fact already used in cognitive therapy as a strategy to treat problem gambling (Ladouceur & Walker, 1996). Multiple studies have also shown that correcting erroneous beliefs by prevention messages is relevant to prevent problem gambling (Benhsain, Taillefer, & Ladouceur, 2004;Cloutier, Ladouceur & Sévigny, 2006;Floyd, Whelan, & Meyers, 2006;Jardin & Wulfert, 2009;Martinez, Le Floch, Gaffié, & Villejoubert, 2011;Steenbergh et al, 2004). For example, messages reminding the predominance of chance on the outcome of the game in a session of gambling limit risk-taking of the gamblers (Martinez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to slot machines, lotteries, and bingo, which can be viewed as games of pure chance such that any perception of skill is an unrealistic expectance of personal success (Cabot, Light, & Rutledge, 2009) or an illusion of control (Dykstra & Dollinger, 1990;Langer, 1975;Martinez, Le Floch, Gaffié, & Villejoubert, 2011), Hold'em is often conceptualized and viewed as a sport or even career, in which players can control the outcome through motivation, strategy, and skill (McMullan & Kervin, 2011). Undergraduate students tend to spend more money on games in which skill is perceived as an important factor in comparison to those games perceived to be more dependent on chance (Kairouz, Paradis, & Monson, 2015).…”
Section: Introductionmentioning
confidence: 99%